MODEL PEMBELAJARAN MULTILITERASI PADA PEMBELAJARAN MEMBACA PEMAHAMAN DI KELAS IV SEKOLAH DASAR - Ristika Ristika (Universitas Majalengka, 2019)
This research is motivated by the low reading ability of students in Indonesian language learning. This study aims to improve students' reading comprehension skills in grade IV of the Baitul Jannah School Bandar Lampung Integrated Islamic Elementary School by using a multiliterasi learning model. The research method used by researchers is classroom action research in collaboration with grade IV teachers at SDIT Baitul Jannah School with a total of 25 students in class IV consisting of 15 female students and 10 male students. This research took place in 3 cycles, each cycle consisting of 3 actions. The techniques used in data collection were the ability to read comprehension tests, observations, interviews, documentation, and field notes. The results showed that the multi-literacy learning model could improve students' reading comprehension skills in grade IV SDIT Baitul Jannah School in Bandar Lampung.